ZnO films grown by laser ablation with and without oxygen CVD - Bentes, L. (2007)
In the present work we have studied the properties of zinc oxide (ZnO) thin films grown by laser ablation of ZnO targets under different substrate temperature and background oxygen conditions. The ZnO layers were deposited with a Pulsed Laser Deposition (PLD) system on pre-nitrided (0001) sapphire (Al2O3), using the base line of a Nd:YAG laser at 1064 nm. The films were characterized by different structural and optical methods, including X-ray diffraction (XRD), scanning electron microscopy (SEM), optical transmission spectroscopy, and steady-state photoluminescence (PL). XRD analysis with rocking curves and θ–2θ scans indicates preferential growth along the c-axis direction with a full width at half maximum (FWHM) smaller than 1.5∘. Low-temperature photoluminescence (PL) showed strong excitonic emission near 3.36 eV between 9 and 65 K.